THE EFFECT OF COMPANY SIZES, THE NUMBER OF BOARD OF COMMISSIONERS, BOARD OF DIRECTORS COMPETENCE AND AUDIT COMMITTEES ON TAX MANAGEMENT - Lia Setiawati; Icih Icih; Asri Suangga (STIESA Press, 2019)
This study aims to examine the effect of company size, the number of boards of commissioners, compensation of the board of directors, and audit committee on tax management which is measured using two measures, namely effective tax rates (ETR) and cash effective tax rates (CETR). The population of this research is all companies in the manufacturing sector which are listed on the Indonesia Stock Exchange from 2011 to 2014. The sample selection technique uses purposive sampling to obtain samples that fit the criteria of 18 companies. Tests conducted in this study use multiple linear regression test which includes the classic assumption test, F test, t test and coefficient of determination (R2) and to analyze data using SPSS Version 22. The results of this study indicate that partially company size variables have a significant positive effect on tax management as measured by ETR and CETR, variable number of the board of commissioners has a significant negative effect on tax management as measured by ETR, but the variable number of board of commissioners does not affect the tax management that measured by CETR. And the proportion of compensation of the board of directors and audit committee has no effect on tax management as measured by ETR or CETR. Simultaneously the size of the company, the number of the board of commissioners, compensation of the board of directors and the audit committee together affect the tax management as measured using ETR and CETR.